(untitled) (Research, Society and Development, 2022)
Objective: to survey existing knowledge in the literature about nursing care for patients with heart failure. Method: This is an Integrative Literature Review carried out through six stages, for the elaboration of the research question, the PICo strategy was used and the chosen database was the Virtual Health Library (BVS), data extraction was performed using the Ursi form. Data analysis and interpretation were discussed throughout the text. Results: a final sample of ten articles was obtained, it was noticed that part of the selected articles sought to research on nursing care in hospitalized patients with HF, seeking the main interventions and nursing diagnoses. While another part explored the role of nurses in monitoring patients with HF in the home environment. area. Conclusion: It was noticed that the theme heart failure is and has been of great relevance for nursing, given the frequency of articles produced in Brazil and in the world. When reviewing the literature, it was seen that nursing care for patients with heart failure is divided into two environments : hospital environment and outpatient/home environment.